Motivasi Siswa dalam Mengikuti Kegiatan Ekstrakurikuler Futsal - Muh Wahyu Solehudin; Adiman Adiman; Dewi Wahyuni (Indonesian Journal of Physical Education and Sport Science, 2023)
Study purpose. This study aims to determine students' motivation in participating in futsal extracurricular activities at SMPN 18 Kota Cirebon, both from intrinsic and extrinsic aspects. Materials and Methods. The research design used was quantitative descriptive, with the aim of systematically, factually, and accurately describing students' motivation in participating in the activity. Data were collected through the distribution of questionnaires to students participating in the futsal extracurricular activity, then analysed descriptively using percentages. Results. The results of the study indicate that students' motivation in participating in futsal extracurricular activities varies, with 3 students (12.5%) having very low motivation, 9 students (37.5%) having low motivation, 7 students (29.17%) having high motivation, and 5 students (20.83%) having very high motivation. Conclusion. Thus, it can be concluded that student motivation in participating in futsal extracurricular activities at SMPN 18 Kota Cirebon tends to be dominated by the low category, although some students show high and very high motivation.